From the fairground sensorium to the digitalization of bodily entertainment: commercializing multisensory entertainments involving the bodily senses - Spence, C (Taylor and Francis, 2022)
Entertaining the bodily senses by means of the deliberate stimulation of the proprioceptive, kinesthetic, and/or vestibular senses/systems has long been the focus of many of the (mechanical) rides found on the fairground and at the theme park. Although the history of kinaesthetic thrills and proprioceptive pleasures stretches back to the turn of the 20th Century, and, despite the growing interest in digital stimulation (e.g. virtual reality, the Metaverse, etc.), little progress has, as yet, been made in terms of effectively stimulating the bodily senses digitally (e.g. in the home environment) as part of a commoditization of multisensory entertainments. Indeed, it may simply not be possible to digitally elicit the total immersion that one experiences in a well-designed theme-park/fairground ride. Nevertheless, approaching that goal will likely require a recognition of the fundamentally multisensory nature of the experience delivered by the unique sensorium that one finds on the working fairground. And, as we will see later, the contribution of the non-bodily senses is something that is often neglected when researchers have studied such bodily sensations in the laboratory, or else foregrounded them in an artistic, setting.